Telemedicine: an important aid to perform high-quality endoscopic retrograde cholangiopancreatography in low-volume centers - Påhlsson, H. I.; Groth, K.; Permert, J.; Swahn, F.; Löhr, M.; Enochsson, L.; Lundell, L.; Arnelo, U. (Endoscopy, 2013)
Background and study aims: The aim of this study was to investigate whether telemedicine can help to ensure high-quality endoscopic retrograde cholangiopancreatography (ERCP) in patients living in rural areas. The study was conducted by investigators from two centers: the Karolinska University Hospital, a high-volume center which provided the teleguided support, and the Visby District Hospital, a low-volume center.Patients and methods: From September 2010 to August 2011, 26 ERCP procedures performed at a district hospital were teleguided by an experienced endoscopist at the Karolinska University Hospital. To ensure patient data protection, all communication went through a network (Sjunet) that was separate from the Internet and open only to accredited users. The indications for ERCP were common bile duct stones (n = 12), malignant strictures (n = 12), and benign biliary strictures (n = 2). In 15 cases, this was the patient’s first ERCP procedure. Results: The common bile duct was successfully cannulated in all 26 teleguided procedures. The local endoscopist scored the teleguided support as crucial for the successful outcome in 8 /26 cases, as an important factor in 8, and as being of less importance in the remaining 10. In the eight cases where the teleguided support was judged to be crucial, six subsequent percutaneous transhepatic cholangiography procedures and two repeat ERCPs were avoided. The overall cannulation rate at the district hospital improved from 85 % to 99 % after teleguided support was introduced. No procedure-related complications occurred. Conclusion: Distant guidance of advanced ERCP procedures in a low-volume center, through teleguided support from a high-volume center, has the potential to improve the quality of care, as reflected in high cannulation rates and the ability to complete the scheduled interventions.